2017
DOI: 10.1097/jac.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

Reporting From the Front Lines

Abstract: Alternative payment models have been proposed as a way to facilitate patient-centered medical home model implementation, yet little is known about how payment reform translates into changes in care delivery. We conducted site visits, observed operations, and conducted interviews within 3 Federally Qualified Health Center organizations that were part of Oregon's Alternative Payment Methodology demonstration project. Data were analyzed using an immersion-crystallization approach. We identified several care deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Limited reimbursement of non-clinical staff is a major limitation to the dissemination of team-based models that expand the role of these allied health workers to aid patients in diabetes care management. Innovative payment models, such as the Federally Qualified Health Center Alternative Payment Methodology in Oregon [ 41 ], which incentives containment of total costs of care, might stimulate the use of team-based diabetes care management models that include CHWs and MAs, as well as peers [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limited reimbursement of non-clinical staff is a major limitation to the dissemination of team-based models that expand the role of these allied health workers to aid patients in diabetes care management. Innovative payment models, such as the Federally Qualified Health Center Alternative Payment Methodology in Oregon [ 41 ], which incentives containment of total costs of care, might stimulate the use of team-based diabetes care management models that include CHWs and MAs, as well as peers [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Past research has documented that health centers have sought additional funds over and above PPS and additional flexibility under FQHC APM to reduce provider burnout while delivering the full range of team-based care services with a variety of care team members under a patient-centered medical home care model. 25 Given that early VBP models related to hospital readmissions and Medicare ACOs disadvantaged safety-net providers, it is critical to redesign health center payment with a keen eye for avoiding adverse consequences for these important safety-net providers while mitigating, rather than exacerbating, disparities for the patients that health centers serve. [26][27][28]…”
Section: Current Health Center Paymentmentioning
confidence: 99%
“…6 , 7 By removing incentives to achieve a certain volume of visits, capitated models may permit clinicians (and practices) the time and flexibility to more effectively partner with patients on preventive care. 8 Capitation may also promote activities that support prevention and comprehensiveness, such as education and counseling on lifestyle factors, and team members, such as health coaches and peer navigators, who are either not captured or nonbillable under FFS. Indeed, evidence from the 1990s suggested that capitation was associated with a greater likelihood to receive health counseling and other preventive services.…”
Section: Introductionmentioning
confidence: 99%